Implementasi Kebijakan Program Magang MSIB Batch 5 Dalam Meningkatkan Kemampuan Project Business Researcher di PT Indekstat Konsultan Indonesia - Putri Dewanti, Arinta; Abdul Rahman; Nida Handayani (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2024)
The Merdeka Learning Program at Kampus Merdeka is a flexible learning model in higher education designed to encourage innovative learning and adapt to student needs. One of them is an internship program at MSIB partner companies, which is an initiative of Kampus Merdeka to help students prepare for the world of work. PT Indekstat Konsultan Indonesia is one of the partners of this program, with the aim of improving the quality of soft skills and hard skills to be able to work culturally to meet the needs of the capabilities of researchers who are ready to work in the research and data science industry.  This research uses a qualitative case study approach, including interviews, observation, documentation, and review of relevant literature. The theory employed is George C. Edward III with signs of successful implementation, which are: (1) communication, (2) resources, (3) disposition, and (4) bureaucratic structure. The results showed that PT Indekstat Konsultan Indonesia has not implemented the MSIB Batch 5 program policy optimally.